Attitudes of Saudi Arabian Undergraduate Medical Students towards Health Research - Sara M. Al-Hilali; Eman Al-Kahtani; Babar Zaman; Rajiv Khandekar; Abdullah Al-Shahri; Deepak P. Edward (Sultan Qaboos University Medical Journal, 2016)
Objectives: This study aimed to evaluate attitudes, perceptions and perceived barriers towards health research among Saudi Arabian undergraduate medical students. Methods: This cross-sectional study took place between August and October 2014 and included 520 students from five medical schools across Saudi Arabia. An anonymous online survey with 21 close-ended questions was designed to assess students’ attitudes towards research, contribution to research-related activities, awareness of the importance of research, perception of available resources/opportunities for research, appreciation of medical students’ research contributions and perceived barriers to research. Responses were scored on a 5-point Likert scale. Results: A total of 401 students participated in the study (response rate: 77.1%). Of these, 278 (69.3%) were female. A positive attitude towards research was reported by 43.9% of the students. No statistically significant differences were observed between genders with regards to attitudes towards and available resources for research (P = 0.500 and 0.200, respectively). Clinical students had a significantly more positive attitude towards research compared to preclinical students (P = 0.007). Only 26.4% of the respondents believed that they had adequate resources/opportunities for research. According to the students, perceived barriers to undertaking research included time constraints (n = 200; 49.9%), lack of research mentors (n = 95; 23.7%), lack of formal research methodology training (n = 170; 42.4%) and difficulties in conducting literature searches (n = 145; 36.2%). Conclusion:Less than half of the surveyed Saudi Arabian medical students had a positive attitude towards health research. Medical education policies should aim to counteract the barriers identified in this study.